REDESAIN RUANG TERBUKA HIJAU KAMPUS UNSRAT BERDASARKAN EVALUASI KENYAMANAN TERMAL DENGAN INDEKS DISC - Saroinsong, Fabiola B.; Kalangi, J. I.; Babo, Prestin (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ Outdoor spaces are important to sustainable cities because they accommodate outdoor activities and contribute greatly to the quality of urban living.During the last decade, interest in the assessment of thermal comfort has increased because of climate changes and increased heat stress in cities. Greenspaces that provide a pleasurable thermal comfort experience for users effectively improve their quality of livability and productivity. However, current investigations lack a general framework for the use of thermal comfort assessment, such as in making master plan or designing better greenspace. This paper discusses greenspace of Sam Ratulangi University Campus relating to thermal comfort. It provides knowledge of thermal comfort investigation and landscape design review. The results of thermal comfort assessment, among 11 observed plots, only greenspace at FMIPA is categorized as comfortablespot. Greenspaces at FAPET and FEB are not really comfortable, those at BNI and FKM A and FKM B are not comfortable and those at FATEK, FAPERTA, FISIP, FH, FKM A are categorized as very uncomfortable spots. We suggest some options for redesigningof uncomfortable and very uncomfortable greenspace spots.Keywords: greenspace, outdoor, termal comfort